(untitled) (ENTHYMEMA, 2015)
The aim of this article is to analyze the interpretation of Carlo Michelstaedter’s thought defined by Gianni Carchia. Discussing the Carchia’s approach to Michelstaedter’s philosophy, we will show up some problematic points, like the relation between language and rhetoric or that between life and being. Cloncluding, we will try to define the complex hermenutical relation which Gianni Carchia maintains with the Michelstaedter’s text. Lo scopo del presente articolo è quello di analizzare l’interpretazione del pensiero di Carlo Michelsatedter offerta da Gianni Carchia. Discutendo l’approccio di carchia alla filosofia di Michelstaedter, sottolineeremo alcuni passaggi problematici, come la relazione fra lingua e retorica o quella fra vita ed essere. In conclusione, cercheremo di definire la complessa relazione ermeneutica che Gianni carchia intrattiene col testo di Michelstaedter